2013
DOI: 10.1016/j.cca.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin on CYP3A4 and CYP3A5 mRNA expression in mononuclear cells and CYP3A activity in hypercholeresterolemic patients

Abstract: It is likely that cholesterolemia status changes promoted by atorvastatin play a role in regulating CYP3A4 and CYP3A5 mRNA expression in PBMCs, as well as CYP3A activity. CYP3A5*3C (AGT haplotype) also contributes for the variability of CYP3A5 mRNA levels in PBMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Regarding the CYP3A4 *1B, we reported no association of this allele with lowdensity lipoprotein (LDL) cholesterol response [67], which was in agreement with a previous report in the Brazilian population using statins where efficacy and safety of the treatment were not affected by the CYP3A4*1B in patients using simvastatin [69].…”
Section: Cyp3a4supporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the CYP3A4 *1B, we reported no association of this allele with lowdensity lipoprotein (LDL) cholesterol response [67], which was in agreement with a previous report in the Brazilian population using statins where efficacy and safety of the treatment were not affected by the CYP3A4*1B in patients using simvastatin [69].…”
Section: Cyp3a4supporting
confidence: 92%
“…As earlier stated in this review, we reported that haplotypes formed by CYP3A4*1B and the CYP3A5 variants, *3C and *1D, affect the gene expression of CYP3A5 mRNA in PBMC from hypercholesterolemic patients [67]. Moreover, a previous report of our research group related a lower decrease of LDL cholesterol values in non-African hypercholesterolemic individuals with the genotypes CYP3A5*3C/3C and CYP3A5*1D/1D [72].…”
Section: Cyp3a5supporting
confidence: 71%
See 1 more Smart Citation
“…The same report indicated that lovastatin acts on the expression of CYP 2C9 exactly in reverse order that atorvastatin does. Another study which took place on human patients showed that atorvastatin administration increased remarkably CYP 3A4 and 3A5 mRNA expression in peripheral blood mononuclear cells of hypercholesterolemic patients (Willrich et al, 2013). One more explanation for different responses of various cells and tissues to atorvastatin may be related to its biotransformation profile.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown susceptibility to inhibitors and inducers of CYP3A4 to produce increased or decreased plasma concentrations respectively 3 . The usage of herbal therapies along with prescription and Over-TheCounter (OTC) medications is increasing day by day.…”
mentioning
confidence: 99%